Determination of the thermal and mechanical properties for materials containing epoxidised palm oil, clay and fly ash - Balo, Figen; Yucel, H. Lutfi; Ucar, Aynur (Taylor & Francis Ltd, 2010)
In this study, the thermal conductivity and mechanical properties of samples produced by mixing waste fly ash (FA), natural clay (C) and epoxidised palm oil (EPO), the renewable material, were experimentally investigated. FA and C were used as the raw materials for sample production and the sample EPO was the binder. The experimental results revealed that higher proportions of both FA and EPO reduced the thermal conductivity coefficient, mass, compressive strength and tensile strength of the samples. The lowest, and therefore best, value of thermal conductivity obtained was 0.255 W/m K and this was measured for the sample with a 70% FA to 30% C ratio mixed with 50% EPO and processed at 200(circle)C. However, this sample had the lowest compression and tensile strength values, 1.5 and 0.428 MPa, respectively, and the highest abrasion loss at 5.55%. The highest compression and tensile strengths and the lowest value of abrasion loss, at 4.26 MPa, 0.722 MPa and 1.27%, respectively, were observed for the sample with a 30% FA to 70% C ratio mixed with 40% EPO and processed at 160(circle)C. However, this material combination had the highest thermal conductivity at 0.428W/m K.
Keywords: fly ash; epoxidised palm oil; waste minimisation; environmentally conscious manufacture; biomass materials